Kampanye Advokasi Kesehatan Berbasis Precede-Proceed untuk Pencegahan dan Pengendalian Hipertensi di Wilayah Kerja Puskesmas Pannambungan Makassar - Asyima Asyima; Fatmawati Amir; Susi Rabuana; Yusriani Yusriani; Andi Asrina; Fairuz Prihatin Idris (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Hypertension is a significant public health problem in the working area of Puskesmas Pannambungan Makassar. Data indicates high prevalence of hypertension with low case detection and treatment rates in the community, highlighting the need for comprehensive health education and advocacy efforts. This community service activity aims to implement a health advocacy campaign based on the PRECEDE-PROCEED framework to improve community knowledge, attitudes, and behaviors in hypertension prevention and control in the working area of Puskesmas Pannambungan Makassar. Community service was carried out using a participatory approach applying the PRECEDE-PROCEED framework through several stages: (1) community needs analysis, (2) stakeholder mapping, (3) design and implementation of multi-channel campaigns, and (4) monitoring and evaluation. Activities involved the community, Puskesmas Pannambungan health workers, health cadres, and local stakeholders. Community service activities successfully identified six critical hypertension issues in the target area, conducted Posbindu health cadre training, blood pressure screening campaigns, healthy lifestyle counseling, and multi-channel educational media dissemination. Active community participation and cross-stakeholder synergy significantly improved program outcomes. PRECEDE-PROCEED based health advocacy campaigns are effective as a systematic approach to improving hypertension awareness and control in the working area of Puskesmas Pannambungan Makassar. Program sustainability requires commitment from all stakeholders and adequate resource allocation.